Free‐Space Optical Backplane Prototype for Telecommunication Equipment in the Petabit/s Range. (December 2013) - Maggio, Santo; Zhang, Qingnan; Zhao, Zhongxu; Leven, Andreas; Varma, Eve L.
Abstract Dramatically increasing telecommunication equipment bandwidth motivates exploration of new technologies for backplane implementation. Hence, it is necessary to consider optical backplane implementations for realizing petabit/s switches. Current optical backplane implementations usually guide the light from source to destination with embedded fibers. In this paper we present a new implementation variant for an optical backplane. wherein free space is used as the optical signal medium. This realization just requires fixed mirrors in the rear of the line cards and thus the solution is very cost‐effective. The transmitter and receiver are realized using high‐speed lasers and photodiodes, and each individual link can transport 25 Gb/s of traffic. Some experimental results are also presented. As an evolutionary step for increased bandwidth, the paper considers the use of an array of links. In this case, we also evaluate the possibility of implementing the parallel transmitters and receivers in an integrated device, which would further reduce space, power consumption and cost. © 2013 Alcatel‐Lucent.